Differential Modulation of Thresholds for Intracranial Self-Stimulation by mGlu5 Positive and Negative Allosteric Modulators: Implications for Effects on Drug Self-Administration - Olive, M. Foster (Frontiers in Pharmacology, 2012)
Pharmacological manipulation of the type 5 metabotropic glutamate (mGlu5) receptor alters various addiction related behaviors such as drug self-administration and the extinction and reinstatement of drug-seeking behavior. However, the effects of pharmacological modulation of mGlu5 receptors on brain reward function have not been widely investigated. We examined the effects of acute administration of positive and negative allosteric modulators (PAMs and NAMs, respectively) on brain reward function by assessing thresholds for intracranial self-stimulation (ICSS). In addition, when acute effects were observed, we examined potential changes in altered ICSS thresholds following repeated administration. Male Sprague-Dawley rats were implanted with bipolar electrodes into the medial forebrain bundle and trained to respond for ICSS, followed by assessment of effects of mGlu5 ligands on ICSS thresholds using a discrete trials current intensity threshold determination procedure. Acute administration of the selective mGlu5 NAMs MTEP (0, 0.3, 1 or 3 mg/kg) and fenobam (0, 3, 10, or 30 mg/kg) dose-dependently increased ICSS thresholds (~70% at the highest dose tested), suggesting a deficit in brain reward function. Acute administration of the mGlu5 PAMs CDPPB (0, 10, 30 and 60 mg/kg) or ADX47273 (0, 10, 30 and 60 mg/kg) was without effect at any dose tested. When administered once daily for 5 consecutive days, the development of tolerance to the ability of threshold-elevating doses of MTEP and fenobam to increase ICSS thresholds was observed. We conclude that mGlu5 PAMs and NAMs differentially affect brain reward function, and that tolerance to the ability of mGlu5 NAMs to reduce brain reward function develops with repeated administration. These brain reward deficits should be taken into consideration when interpreting acute effects of mGlu5 NAMs on drug self-administration, and repeated administration may be an effective method to reduce these deficits.